DIPG-26. MOLECULAR DETERMINANTS OF RESPONSE TO RADIOTHERAPY IN DIPG: A CLINICAL AND IN VITRO STUDY. Issue 2 (22nd June 2018) - Werbrouck, Coralie; Evangeslista, Cláudia C S; Barret, Emilie; Puget, Stéphanie; Grill, Jacques; Debily, Marie-Anne; Castel, David
Abstract: Diffuse intrinsic pontine gliomas (DIPG) are the most severe and common form of malignant brain tumours in children and adolescent. Radiotherapy is the only validated treatment, albeit only bringing a transient symptom relief followed by a constant subsequent progression within a variable delay. We previously identified a heterogeneous response to radiotherapy at diagnosis in DIPG patients depending on the type of mutated histone H3 (Castel et al., 2015 & 2016). We thus hypothesized that there are possible molecular determinants of this initial response, and evaluated the radiosensitivity of a compendium of 13 treatment-naïve cellular models of DIPG deriving from stereotactic biopsies at diagnosis. Our results show a heterogeneous response of DIPG cells to RT in vitro correlating with the duration of the clinical response in the corresponding patients. This phenomenon thus implies a cell-autonomous response, and we decided to confront radioresistance with the molecular profiles of the corresponding cells. It appears that the main driver of resistance to irradiation in DIPG is the inactivation of TP53, and not the type of mutated histone per se. We are currently validating this result in isogenic DIPG cells with or without functional TP53, and studying the underlying molecular mechanisms that could explain the differences in radiosensitivity of these tumour cells. By confronting tumour molecular data with clinical responses to RT in a monocentric retrospective cohort, we are able to consolidate our in vitro prediction and propose new possible stratifications in DIPG with respect to response to therapy.